1986
DOI: 10.1002/aja.1001760209
|View full text |Cite
|
Sign up to set email alerts
|

Structural and histochemical aspects of epidermis development of fetal porcine skin

Abstract: Epidermal development of fetal porcine skin was studied in fetuses from 41 days of gestation until birth with scanning and electron microscopy techniques as well as histochemical methods, including immunohistochemistry. The porcine fetus develops a relatively thick and solid multilayered cover of epidermal cells, which is not lost before birth. It consists of tightly packed cells of the periderm and the stratum intermedium. The periderm cells are totally filled with filamentous proteins; in the intermediate ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 32 publications
0
4
0
3
Order By: Relevance
“…Finally, a recent study has confirmed the potential for dermal toxicity as these fuels were shown to cross the epidermal barrier for potential access to the systemic circulation . The use of pig skin in dermatotoxicological research has been widely accepted due to its morphological and physiological similarities to human skin (Bartek et al, 1972;Meyer et al, 1986;Monteiro-Riviere, 1986;Simon and Maibach, 2000). Furthermore, the use of keratinocyte cell cultures have been gaining acceptance as an alternative to animal studies for such research (Roguet, 1998;Bernstein and Vaughan, 1999).…”
Section: Dg Allen Et Al / Toxicology Utters 000 (2001) 000-000mentioning
confidence: 99%
“…Finally, a recent study has confirmed the potential for dermal toxicity as these fuels were shown to cross the epidermal barrier for potential access to the systemic circulation . The use of pig skin in dermatotoxicological research has been widely accepted due to its morphological and physiological similarities to human skin (Bartek et al, 1972;Meyer et al, 1986;Monteiro-Riviere, 1986;Simon and Maibach, 2000). Furthermore, the use of keratinocyte cell cultures have been gaining acceptance as an alternative to animal studies for such research (Roguet, 1998;Bernstein and Vaughan, 1999).…”
Section: Dg Allen Et Al / Toxicology Utters 000 (2001) 000-000mentioning
confidence: 99%
“…Porcine skin is morphologically (17,19,20,26) and histochemically (16,33,42) similar to human skin and has been utilized as a model for the study of percutaneous absorption and toxicity ( 1,31 ). The IPPSF, an alternative in vitro model, is morphologically similar to human skin (22) and correlates well to in vivo (5,40) and human absorption (34) data.…”
Section: Introduction Sulfur Mustard (Bis [2-chloroethyl Sulfide] Hd)mentioning
confidence: 98%
“…This later study demonstrates the need to corroborate in other species some of the information generated by the murine model and suggests that the swine models can more accurately reflect humans skin than other mouse or in vitro studies. More specifically, the porcine integument is morphologically (23)(24)(25)(26)(27)(28)(29)(30)(31), histochemically (28)(29)(30)(31)(32)(33), biochemically, and biophysically similar to human skin and has been used as a model for drug toxicity and percutaneous absorption studies. Swine skin resembles human skin in having a sparse hair coat and a relatively thick epidermis with similar epidermal turnover kinetics, number of hair follicles, lipid composition and carbohydrate biochemistry, lipid biophysical properties, and the arrangement of dermal collagen and elastic fibers (34)(35)(36)(37)(38)(39)(40)(41).…”
Section: Introductionmentioning
confidence: 99%